Unconscious Mind Application in Class-Learning To Increase Gen Z Intention in Becoming Entrepreneur - Iskandarini (Indonesian Journal of Business and Entrepreneurship (IJBE), 2021)
This research is based on a true experiment of two cohorts in entrepreneurial class at Universitas Sumatera Utara where nowadays the learning materials must be active and stimulate the creativity of Generation (Gen) Z to be more interested to become more independent and entrepreneurial after they graduate. The unconscious mind method was grafted into the teaching material after the consideration that previous material has been more conscious mind. Unconscious mind material was given to fifty students during four meetings with different topics combined with conscious mind material, action, and evaluation. As a comparison, some of the other students who also consisted of fifty students were given materials based on the current syllabus which contained only conscious mind material. The results showed that unconscious mind application in class-learning had performed higher intention to later become entrepreneurs than control groups who tended to decline in interest. Keywords: entrepreneurial intention, entrepreneurship, entrepreneurship teaching method, Gen Z, the unconscious mind